Dominant regions and drivers of the variability of the global land carbon sink across timescales. (8th May 2018) - Zhang, Xuanze; Wang, Ying‐Ping; Peng, Shushi; Rayner, Peter J.; Ciais, Philippe; Silver, Jeremy D.; Piao, Shilong; Zhu, Zaichun; Lu, Xingjie; Zheng, Xiaogu
Abstract: Net biome productivity (NBP) dominates the observed large variation of atmospheric CO2 annual increase over the last five decades. However, the dominant regions controlling inter‐annual to multi‐decadal variability of global NBP are still controversial (semi‐arid regions vs. temperate or tropical forests). By developing a theory for partitioning the variance of NBP into the contributions of net primary production (NPP) and heterotrophic respiration ( R h ) at different timescales, and using both observation‐based atmospheric CO2 inversion product and the outputs of 10 process‐based terrestrial ecosystem models forced by 110‐year observational climate, we tried to reconcile the controversy by showing that semi‐arid lands dominate the variability of global NBP at inter‐annual (<10 years) and tropical forests dominate at multi‐decadal scales (>30 years). Results further indicate that global NBP variability is dominated by the NPP component at inter‐annual timescales, and is progressively controlled by R h with increasing timescale. Multi‐decadal NBP variations of tropical rainforests are modulated by the Pacific Decadal Oscillation (PDO) through its significant influences on both temperature and precipitation. This study calls for long‐term observations for the decadal or longer fluctuations in carbon fluxes to gain insights on the future evolution of global NBP, particularly in the tropical forests that dominate the decadal variability of land carbon uptake and are more effective for climate mitigation. Abstract : Contributions of variance in regional NBP at different timescales and regional contributions to variance of global NBP at difference timescales.